Technique In Teaching Reading To The Sixth Year Students Of SD N 2 Tlogorandu - Sulistiyono, Maulana, Aryati Prasetyarini, S.Pd, M.Pd, Dr. Anam Sutopo, M.Hum (2013)
The research aims at observation of teaching English especially teaching reading comprehension at SD N 2 TLOGORANDU. The research was conducted at the elementary students in 2012. This research paper is intended to describe a descriptive qualitative method on teaching reading comprehension in the second year of SD N 2 TLOGORANDU. Natural Approach method adopted to teach reading is to enable students in active in practicing English language. The type of the study is descriptive qualitative method. The subjects of the study were the sixth year students of SD N 2 TLOGORANDU. The data collected is the phenomena or facts concerning of the technique in teaching reading to the sixth year student. The data collecting method was done employing observation, interview, documentation and questionnaire techniques. The data analysis was undertaken by describing the data collected, classifying the difficulties faced by the teacher and the students in teaching and learning reading using communicative approach, determining the strength and weakness of teaching reading and interpreting the analyzed data. From the research finding, the objective of teaching reading comprehension in SD N 2 TLOGORANDU covers two goals: the general objective is to the student develop the mentality of the nation and the specific objective is are expected to have a good knowledge about it. while the techniques of teaching reading comprehension, are : group discussion, silent reading, reading aloud, and question and answer. And the process of teaching reading comprehension, this paper using three process, there are: pre-reading activity, while-reading activity, and post-reading activity. The writer also found the strength and weakness in this material.